Causes and Consequences of Rural Urban Migration: The Case of Sodo Town, Wolaita Zone - Zergaw, Sara; Asale, Alemayehu (International Journal of Publication and Social Studies, 2019)
The study was about Causes and Consequences of Rural Urban Migration: the case of Sodo town, Wolaita Zone, SNNPR, Ethiopia with specific objectives of to assess factors that aggravate rural urban migration; and to examine the consequences of rural urban migration in study area. Two stage sampling technique was used to select the 40 sample respondents from the total population. As far as the causes of migration is concerned, 35%,32.5%.17.5% and 15% were found to migrate due to some reasons like resource conflict, lack of job, lack of housing service, and lack of food respectively. As a result, local, regional or federal governments should give due emphasis for strengthening indigenous and formal institutions in such a way that they able to mange resource conflicts; and ensure transformation of agriculture in which case productivity would to increase food supply; and improve the lively hood of rural people. The study has also revealed about 47.5% and 25% of the total respondents were female and children below 15 years of age which shows especial emphasis should be given to educate children and to empower women. Further, about 62.5% and 67.5% were landless and unemployed as a result which the local, regional and federal governments should place especial attention to reduce unemployment by mobilizing rural people to effectively handle or manage their land and ensure productivity via increased employment there.